Suitable Dietary Protein and Energy Levels of Three Cross Breed Chicken for Roasted Chicken Production - Kwanhian, Ekapong; Attamangkune, Seksom; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2021)
The study was conducted in open house using 3,600 Three cross breed chickens. Feed and water were provided ad libitum throughout the experiment. During 1-4 weeks of age, all birds were fed diets containing 20% protein and 3,000 kcal metabolizable energy/kg. Thereafter, all birds were fed diets containing 3 levels of protein (18.0, 17.5 and 17.0%) and 3 levels of metabolizable energy (3,100 3,000 and 2,900 kcal/kg) until they reached 1.30 kg average body weight. Each treatment consisted of 8 replicates (4 males and 4 females) with 50 birds per replicates. The experimental design was 3 x 3 factorial in randomized complete block design (Factorials in RCBD) with sex as block. There was no significant interaction of protein and metabolizable energy levels on growth performance and carcass quality of Three cross breed chickens (P>0.05). The reduction of protein level decreased body weight gain (P=0.1482) and increased feed conversion ratio (P=0.1421) of three cross breed chickens. In addition, % abdominal fat tended to increase with a decrease of protein and metabolizable energy (P=0.0503). The lowest feed cost per gain at 1.30 kg body weight of male three cross breed was found in birds fed diet containing 17% protein and 3,000 kcal/kg metabolizable energy (27.92 baht/kg BW). While the lowest feed cost per gain at 1.30 kg body weight of female three cross breed was found in birds fed diet containing 18% protein and 2,900 kcal/kg metabolizable energy (30.13 baht/kg BW).